2023
DOI: 10.1002/alz.13571
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in brain atrophy in dementia with Lewy bodies

Javier Oltra,
Annegret Habich,
Christopher G. Schwarz
et al.

Abstract: INTRODUCTIONSex influences neurodegeneration, but it has been poorly investigated in dementia with Lewy bodies (DLB). We investigated sex differences in brain atrophy in DLB using magnetic resonance imaging (MRI).METHODSWe included 436 patients from the European‐DLB consortium and the Mayo Clinic. Sex differences and sex‐by‐age interactions were assessed through visual atrophy rating scales (n = 327; 73 ± 8 years, 62% males) and automated estimations of regional gray matter volume and cortical thickness (n = 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…The incidence of DLB is greater in men than in women but pathology and clinical features vary with gender (Oltra et al, 2024 ). One recent study using a mouse model of PD showed that α-syn accumulation was age-dependent, but with male mice being more severely affected by α-syn toxicity than females (Lamontagne-Proulx et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of DLB is greater in men than in women but pathology and clinical features vary with gender (Oltra et al, 2024 ). One recent study using a mouse model of PD showed that α-syn accumulation was age-dependent, but with male mice being more severely affected by α-syn toxicity than females (Lamontagne-Proulx et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the prevalence of AD is higher in women [ 197 ]. Sex and gender differences in AD and DLB are not limited to prevalence [ 184 , 198 , 199 ]. Women with LB pathology are at greater risk of underdiagnosis or misdiagnosis [ 184 , 190 ].…”
Section: Call For Diversitymentioning
confidence: 99%